Tumor necrosis factor (TNF) receptor associated periodic syndrome (TRAPS): a rare cause of recurrent fever - Gitte, Sachin; G., Pradhan; M., Santoshi (International Journal of Research in Medical Sciences, 2018)
The one year old male child presented with fever on and off, associated with periorbital swelling and arthritis. Infectious, rheumatological and oncological diagnoses were ruled out. Further follow-up over 4-5 years revealed that, the child continued to have similar episodes every month and investigated for almost all possible causes but no conclusive diagnosis was made. Hence evaluation for rare causes of periodic fever was considered. Genetic testing revealed mutation in a novel variant of TNFRSF1A gene, thus confirming Tumor necrosis factor receptorassociated periodic syndrome (TRAPS). Tumor necrosis factor receptorassociated periodic syndrome (TRAPS) is an autosomal dominant inherited condition of periodic fever and joint pain. Here we are presenting a case of this rare syndrome.